Preparation of a highly active double heteroatom-doped carbon nitride nanozyme and its colorimetric detection application
By introducing a two-heteroatom doping structure into the nanoenzymes, the specific copper-oxygen ratio and the mass ratio of carbon nitride to oxygen are used to successfully improve the catalytic activity and stability of the nanoenzymes, solving the problems of low efficiency and complex preparation of existing nanoenzymes, and achieving a more efficient and economical catalytic effect.
Patent Information
- Application Number
- CN202510237078.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-01
- Publication Date
- 2025-04-01
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The catalytic efficiency of existing nanoenzymes is low, the preparation process is complex, and there is a risk of environmental pollution, making it difficult to apply on industrial scale.
By using melamine and urea as carbon and nitrogen sources, oxalic acid as oxygen sources, and introducing metal salts, the two-heteroatom-doped carbon nitride nanozyme was successfully synthesized, with the copper-oxygen ratio of 1: (20-80), and the mass ratio of carbon nitride to oxygen was 1: (0-0.4).
It significantly improves the peroxidase-like activity of nanoenzymes, has better pH and temperature stability, is suitable for more application scenarios, and reduces application costs.
Smart Images

Figure CN119735174A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of nanozymes, and in particular to the preparation of a highly active double-heteroatom-doped carbon nitride nanozyme and its colorimetric detection application. Background Art
[0002] Graphitic carbon nitride (g-C3N4) has a sheet structure similar to graphite. Its sheets are based on 3-triazine rings (heptazine rings) as the basic structural units. The rings are connected by the terminal N atoms to form an infinitely extended plane. It is considered to be a high-nitrogen-doped graphene. g-C3N4 has been widely used in the field of photocatalysis due to its wide light response range and adjustable band gap structure. In addition, g-C3N4 has been found to have simulated peroxidase activity. According to literature reports, the simulated peroxidase activity of original g-C3N4 is very low. Therefore, exploring how to improve the simulated peroxidase activity of g-C3N4 is still an important research topic.
[0003] Nanozymes have gradually become a viable alternative to natural enzymes. Although a variety of nanozymes have been developed, their catalytic efficiency is generally at a moderate level and lacks specificity. In order to enhance catalytic activity, studies have reported a variety of strategies such as element doping, size or morphology regulation, and composite modification. Among these methods, element doping shows higher efficiency, especially oxygen doping, because oxygen atoms have a higher ability to adsorb electrons than carbon and nitrogen atoms. Therefore, in this patent design, we choose oxygen and metal salts to dope the substrate.
[0004] In the patent with application number CN202211633520.7, an oxygen-doped carbon nitride modified nano calcium peroxide composite photocatalyst is prepared. This method requires the addition of hazardous chemicals such as ammonia and hydrogen peroxide during the preparation process, which will cause pollution to the environment. In the patent with application number CN202410680274.3, oxygen-doped nitrogen-rich carbon nitride is prepared. During the preparation process, 5-amino-1H-tetrazole needs to be calcined and then subjected to a series of treatments. After that, it is mixed evenly with an acidic solution and then subjected to oil bath, de-alcoholization, ultrasound, washing and other operations to obtain nano-scale oxygen-doped nitrogen-rich carbon nitride. The preparation process is complicated. The above-mentioned oxygen-doped carbon nitride materials are all used in the field of photocatalysis, and have the disadvantages of complex preparation methods and harm to the environment, so the large-scale application of catalytic materials in industry is limited. Moreover, in the patents related to double heteroatom-doped carbon nitride, it is rarely used to simulate the activity of peroxidase.
[0005] Traditional natural enzymes are easily inactivated and have high synthesis and purification costs, which limits their application. Although new artificial nanozymes have advantages in stability and synthesis cost, their activity is still far behind that of natural enzymes. Therefore, designing and synthesizing artificial nanozymes with high catalytic activity and low cost is an important challenge facing this field. Summary of the invention
[0006] To solve the above problems, the present invention provides a preparation of a diheteroatom carbon nitride nanozyme and its colorimetric detection application. Using melamine and urea as carbon and nitrogen sources, oxalic acid as an oxygen source, and introducing metal salts, a diheteroatom-doped carbon nitride nanozyme was successfully synthesized. Compared with the nanozymes reported in recent years, the resulting product exhibits significantly enhanced peroxidase-like activity, and compared with natural horseradish peroxidase, it has better pH and temperature stability, and can be applied to more application scenarios.
[0007] To achieve this object, the present invention adopts the following technical solutions: In the first aspect, the present invention provides a di-heteroatom carbon nitride nanozyme, which contains two elements, copper and oxygen. The mass ratio of copper to oxygen in the copper-oxygen diatoms is 1:(20-80), and the mass ratio of carbon nitride to oxygen in the carbon nitride nanozyme is 1:(0-0.4).
[0008] Co-doping metallic copper and non-metallic oxygen into carbon nitride nanozymes greatly improves its specific surface area and makes the element dispersion better. Compared with single metal-doped carbon nitride nanozymes or pure carbon nitride nanozymes, double heteroatom-doped carbon nitride nanozymes exhibit higher peroxide mimetic enzyme activity.
[0009] The present invention significantly improves the activity of carbon nitride nanozyme by limiting the specific copper-oxygen ratio and the ratio of oxygen to carbon nitride.
[0010] The specific point values of 20-80 mentioned above can be selected as 20, 30, 40, 50, 60, 70 or 80 etc.
[0011] The specific point values of 0-0.4 mentioned above can be selected as 0, 0.1, 0.2, 0.3 or 0.4, etc.
[0012] In a second aspect, the present invention provides a method for preparing a double-heteroatom-doped carbon nitride nanozyme as described in the first aspect, the method for preparing the carbon nitride nanozyme comprising mixing and grinding urea, melamine, oxalic acid and a metal salt in a mortar, and obtaining the carbon nitride nanozyme after drying and calcining.
[0013] The method for preparing the double-heteroatom-doped carbon nitride nanozyme used in the present invention is environmentally friendly and economical, and the preparation process is simple and easy, suitable for large-scale promotion. Compared with single-metal-loaded carbon nitride nanozymes and metal-free nanozymes, the double-heteroatom-doped carbon nitride nanozyme of the present invention exhibits significantly enhanced catalytic activity.
[0014] Preferably, the metal salt comprises a divalent copper salt.
[0015] Preferably, the divalent copper salt includes any one of copper nitrate, copper chloride, copper sulfate, copper acetate or copper carbonate, or a combination of at least two thereof.
[0016] Preferably, the copper nitrate comprises copper nitrate trihydrate.
[0017] Preferably, the mass ratio of the urea to melamine is 1:(0-1).
[0018] The specific point value of the above 0-1 can be selected as 0, 0.1, 0.3, 0.5 or 1, etc.
[0019] Preferably, the calcination is carried out by uniform heating, the rate of the uniform heating is 2-4 °C / min (for example, 2 °C / min, 2.2 °C / min, 2.4 °C / min, 2.6 °C / min, 2.8 °C / min, 3 °C / min, 3.2 °C / min, 3.4 °C / min, 3.6 °C / min, 3.8 °C / min or 4 °C / min, etc.), and the endpoint temperature of the uniform heating is 500-600 °C (for example, 500 °C, 510 °C, 520 °C, 530 °C, 540 °C, 560 °C, 570 °C, 580 °C, 590 °C or 600 °C, etc.).
[0020] Preferably, after reaching the terminal temperature, the uniformly heated temperature is maintained for calcination for 3-5 h (e.g., 3 h, 3.2 h, 3.4 h, 3.6 h, 3.8 h, 4 h, 4.2 h, 4.4 h, 4.6 h, 4.8 h or 5 h, etc.).
[0021] Preferably, the protective gas for calcination includes nitrogen or argon.
[0022] In a third aspect, the present invention provides the use of the double-heteroatom-doped carbon nitride nanozyme as described in the first aspect in analytical colorimetric detection.
[0023] As a new type of peroxidase mimic, double heteroatom-doped carbon nitride nanozyme can replace natural enzymes and be used in analytical detection, pollutant removal, biomedicine and other fields. Compared with natural enzymes, the application cost is greatly reduced.
[0024] Other specific point values within the above numerical ranges can be selected and will not be described in detail here.
[0025] Compared with the prior art, the present invention has the following beneficial effects: Using melamine and urea as carbon and nitrogen sources, oxalic acid as an oxygen source, and introducing metal salts, a double heteroatom-doped carbon nitride nanozyme was successfully synthesized. Compared with traditional nanozymes, the product of the present invention exhibits significantly enhanced peroxidase-like activity, and compared with natural horseradish peroxidase, it performs better in pH and temperature stability, and can be applied to more application scenarios. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 SEM (a) and TEM (b) images of double heteroatom-doped carbon nitride. Figure 2 Distribution diagram of O element (a) and Cu element (b) in double heteroatom-doped carbon nitride; Figure 3 XRD patterns of carbon nitride doped with different elements; Figure 4 Comparison of peroxidase activities of double heteroatom-doped carbon nitride in different systems: TMB (a), OPD (b), and ABTS (c); Figure 5 Effect of different temperatures on the activity of double heteroatom-doped carbon nitride peroxidase; Figure 6 Effect of different pH on the activity of double heteroatom doped carbon nitride peroxidase; Figure 7 Specific activity (U / mg) diagram of double heteroatom doped carbon nitride; Figure 8 Steady-state kinetic curve (a) and Lineweaver-Burk linear fitting curve (b) of double heteroatom-doped carbon nitride on TMB; Fig. 9 Steady-state kinetic curve (a) and Lineweaver-Burk linear fitting curve (b) of double heteroatom-doped carbon nitride for H2O2; Fig.10 Comparison of the activities of di-heteroatom-doped carbon nitride peroxidases synthesized with different copper contents; Fig.11 Comparison of the activities of carbon nitride peroxidase doped with different elements; Fig.12 UV-visible absorption spectra (a) and linear fitting diagram (b) of double heteroatom-doped carbon nitride nanozymes in detecting different concentrations of glutathione. DETAILED DESCRIPTION
[0027] To further illustrate the technical means and effects of the present invention, the present invention is further described below in conjunction with the embodiments and drawings. It should be understood that the specific implementation methods described herein are only used to explain the present invention, rather than to limit the present invention.
[0028] If no specific techniques or conditions are specified in the examples, the techniques or conditions described in the literature in the field or the product instructions are used. If no manufacturer is specified for the reagents or instruments used, they are all conventional products that can be purchased through regular channels. Example 1
[0029] In this embodiment, a double heteroatom-doped carbon nitride nanozyme is prepared, and the preparation method includes the following steps: Using the one-step calcination method, 3.6 g of urea, 0.4 g of melamine and 1.6 g of oxalic acid were mixed and ground with 10 mg of copper nitrate trihydrate in a mortar for 30 min. The mixed powder was placed in a porcelain boat and, under the protection of N2 in a tubular furnace, the temperature was raised to 550 ℃ at a rate of 3 ℃ / min and calcined for 4 h to obtain the final black product. Example 2
[0030] In this example, a double heteroatom-doped carbon nitride nanozyme was prepared, which differed from Example 1 only in that the divalent copper salt was changed to 5 mg. Example 3
[0031] In this example, a double heteroatom-doped carbon nitride nanozyme was prepared, which differed from Example 1 only in that the divalent copper salt was changed to 20 mg. Example 4
[0032] This embodiment prepares a double heteroatom-doped carbon nitride nanozyme, which differs from Example 1 only in that the ratio of urea to melamine is changed to 1:0. Example 5
[0033] This embodiment prepares a double heteroatom-doped carbon nitride nanozyme, which differs from Example 1 only in that the ratio of urea to melamine is changed to 1:0.25. Example 6
[0034] This embodiment prepares a double heteroatom-doped carbon nitride nanozyme, which differs from Example 1 only in that the ratio of urea to melamine is changed to 1:1. Example 7
[0035] In this example, a double-heteroatom-doped carbon nitride nanozyme was prepared. The only difference from Example 1 was that the ratio of urea to melamine was changed to 0:1 (0 g urea and 4 g melamine were added). Example 8
[0036] In this example, a copper-doped carbon nitride nanozyme was prepared. The only difference from Example 1 was that the ratio of the total mass of urea and melamine to oxalic acid was changed to 1:0 (3.6 g urea, 0.4 g melamine and 0 g oxalic acid were added). Example 9
[0037] In this embodiment, a double heteroatom-doped carbon nitride nanozyme was prepared. The only difference from Example 1 was that the ratio of the total mass of urea and melamine to oxalic acid was changed to 1:0.1 (i.e., 3.6 g urea, 0.4 g melamine and 0.4 g oxalic acid were added). Example 10
[0038] In this embodiment, a double heteroatom-doped carbon nitride nanozyme was prepared. The only difference from Example 1 was that the ratio of the total mass of urea and melamine to oxalic acid was changed to 1:0.2 (i.e., 3.6 g urea, 0.4 g melamine and 0.8 g oxalic acid were added). Comparative Example 1
[0039] A copper-doped carbon nitride nanozyme was prepared in this comparative example. The difference from Example 1 is that oxalic acid was not added, and only 10 mg of copper nitrate trihydrate, a metal salt, was added. Comparative Example 2
[0040] This comparative example prepared a copper-doped carbon nitride nanozyme, which differs from Example 1 in that no metal salt was added, and only 0.4 g of oxalic acid was added. Test Example 1
[0041] This test example characterizes the properties of the double heteroatom-doped carbon nitride nanozyme obtained in Example 1: (1) Figure 1 Figures (a) and (b) are the SEM and TEM images of double heteroatom-doped carbon nitride, respectively. The material morphology is a block composed of nanosheets, and the metal load is evenly distributed on the sheet. Figure 2 Figures (a) and (b) represent the element distribution diagram of double heteroatom doped carbon nitride, respectively. Figure 2 As shown, it shows that Cu and O are evenly distributed; XRD test shows that all samples have a diffraction peak at 27.4°, where the diffraction peak at 27.4° corresponds to the (002) crystal plane of g-C3N4, which is attributed to the graphene layer stacking of the conjugated aromatic part ( Figure 3 ).
[0042] (2) The peroxidase-like activity of double heteroatom-doped carbon nitride nanozymes was studied by catalytic oxidation of three commonly used chromogenic substrates (TMB, OPD, and ABTS). Figure 4As shown in a, when only TMB is added as a substrate, TMB has no characteristic absorption peak in the wavelength range of 400-800 nm. After adding the double heteroatom-doped carbon nitride nanozyme to the reaction system, the colorless TMB solution quickly turns blue, and the characteristic absorption peak of oxidized TMB appears at 652 nm. The results show that the double heteroatom-doped carbon nitride nanozyme has peroxidase-like activity. Figure 4 As shown in Fig. 2b, when only OPD is added as a color substrate, OPD has no absorption peak in the range of 400-800 nm. However, when mixed with the double heteroatom-doped carbon nitride nanozyme, the reaction system solution changes from colorless to yellow, and the corresponding characteristic absorption peak of the oxidation product appears at 450 nm. Figure 4 As shown in Figure c, the double heteroatom-doped carbon nitride nanozyme can also oxidize ABTS, inducing the color signal to change from colorless to green and produce an absorption peak at 405 nm. The color development reactions of these three different enzyme substrates once again demonstrated the inherent peroxidase-like activity of the double heteroatom-doped carbon nitride nanozyme.
[0043] (3) The catalytic ability of the double heteroatom-doped carbon nitride nanozyme under different temperature conditions was tested. The test included the following steps: (a) A buffer solution containing 0.2 M sodium hydrogen phosphate and 0.1 M citric acid at pH 5 was placed in a water bath at 20°C, 30°C, 35°C, 40°C, 45°C, 50°C, 55°C, 60°C, 70°C and 80°C to maintain a constant temperature; (b) Take 2900 µL of pH 5 warm-bath buffer solution, 30 µL of 1 mol / L H2O2 solution, 60 µL of 25 mmol / L TMB solution and 10 μL of 1 mg / mL double heteroatom-doped carbon nitride nanozyme solution and mix them in a centrifuge tube. The mixing time is controlled within 30 s. (c) Catalytic kinetics curves within 5 min at 652 nm detected by time-driven mode of UV-visible spectrometer.
[0044] The results are as follows Figure 5 As shown, with the increase of temperature, the absorbance value first increases and then decreases, and reaches a peak value at 40°C. Therefore, the catalytic activity of the double heteroatom doped carbon nitride nanozyme is the highest at 40°C.
[0045] (4) The catalytic ability of the double heteroatom doped carbon nitride nanozyme under different pH conditions was tested. The test included the following steps: (a) Prepare buffer solutions containing 0.2 M sodium hydrogen phosphate and 0.1 M citric acid at pH values of 2.2, 3, 4, 5, 6, 7, and 8, respectively; (b) Take 2900 µL of buffer solutions containing 0.2 M sodium dihydrogen phosphate and 0.1 M citric acid of different pH values, 30 µL of 1 mol / L H2O2 solution, 60 µL of 25 mmol / L TMB solution and 10 μL of 1 mg / mL double heteroatom-doped carbon nitride nanozyme solution and mix them in a centrifuge tube; (c) Catalytic kinetics curves within 5 min at 652 nm detected by time-driven mode of UV-visible spectrometer.
[0046] The results are as follows Figure 6 As shown, with the increase of pH value, the absorbance value first increases and then decreases, and reaches a peak value at pH 4. Therefore, the catalytic activity of double heteroatom doped carbon nitride nanozyme is the highest at pH 4.
[0047] (5) Determining the specific activity of the double heteroatom-doped carbon nitride nanozyme, the determination method comprising the following steps: (a) Solutions containing different amounts (0.6-2.0 µg) of nanozymes were placed in 0.2 mol / L NaAc-HAc buffer solution, pH 4; (b) Add 100 µL of 10 mg / mL TMB solution to the centrifuge tube and mix; (c) placing the reaction mixture in a constant temperature water bath and incubating it at 37°C for 1 minute. The water bath is connected to a UV / visible spectrometer. (d) Add H2O2 to the reaction mixture to a final concentration of 1 mol / L and a total volume of 3 mL; (e) Catalytic kinetics curves detected at 652 nm using a UV-visible spectrometer in time-driven mode.
[0048] The results are as follows Figure 7 As shown, the enzyme specific activity of the double heteroatom-doped carbon nitride nanozyme is 38.45 U / mg, which greatly exceeds the activity of most nanozymes reported so far, showing excellent catalytic performance.
[0049] (6) Testing the reaction kinetics of the double heteroatom-doped carbon nitride nanozyme TMB substrate, the testing method comprising the following steps: (a) Take 2900 µL of pH 5 buffer solution containing 0.2 M sodium dihydrogen phosphate and 0.1 M citric acid, 30 µL of 1 mol / L H2O2 solution, 10 μL of 1 mg / mL nanozyme solution, and TMB solutions with final concentrations of 0.1 mmol / L, 0.2 mmol / L, 0.3 mmol / L, 0.4 mmol / L, 0.5 mmol / L, 0.6 mmol / L, 0.7 mmol / L, 0.8 mmol / L, 1 mmol / L, 1.5 mmol / L, 2 mmol / L, 2.5 mmol / L and 3 mmol / L in a centrifuge tube and mix well; (b) Catalytic kinetics curves within 5 min at 652 nm detected by time-driven mode of UV-visible spectrometer.
[0050] The results are as follows Figure 8 As shown in a, as the TMB concentration increases, the initial reaction rate increases. When the TMB concentration increases to a certain concentration, the initial reaction rate tends to the maximum value, which conforms to the typical Michaelis-Menten equation. Figure 8 b shows the kinetic parameter V max and K m The value is calculated by the intercept and slope of the double reciprocal linear fit graph, where K m = 0.41 mM, V max = 65.36x10 -8 M / s.
[0051] (7) The reaction kinetics of the double heteroatom doped carbon nitride nanozyme H2O2 substrate is tested, and the test method includes the following steps: (a) Take 2900 µL of pH 5 buffer solution containing 0.2 M sodium hydrogen phosphate and 0.1 M citric acid, 60 µL of 25 mmol / L TMB solution, 10 μL of 1 mg / mL nanozyme solution, and H2O2 solutions with final concentrations of 0.1 mmol / L, 0.5 mmol / L, 1 mmol / L, 2 mmol / L, 3 mmol / L, 5 mmol / L, 7 mmol / L, 10 mmol / L, 15 mmol / L, 20 mmol / L, 25 mmol / L, 30 mmol / L, 35 mmol / L and 40 mmol / L in a centrifuge tube and mix well; (b) Catalytic kinetics curves within 5 min at 652 nm detected by time-driven mode of UV-visible spectrometer.
[0052] The results are as follows Fig. 9As shown in a, as the H2O2 concentration increases, the initial reaction rate increases. When the H2O2 concentration increases to a certain concentration, the initial reaction rate tends to the maximum value, which conforms to the typical Michaelis equation. Fig. 9 b shows the kinetic parameter V max and K m The value is calculated by the intercept and slope of the double reciprocal linear fit graph, where K m =7.17mM, V max =56.50x10 -8 M / s.
[0053] Depend on Figure 8 and Fig. 9 It can be seen that the oxidation reaction catalyzed by the double heteroatom-doped carbon nitride nanozyme obeys the typical Michaelis-Menten model for the substrates TMB and H2O2, and the copper-oxygen double heteroatom nanozyme has a lower K m value and higher V max , indicating that it has high affinity and catalytic efficiency for the substrates TMB and H2O2, and can efficiently replace natural enzymes. Test Example 2
[0054] In this test example, the catalytic activity of the carbon nitride nanozymes obtained in Examples 1-10 and Comparative Examples 1-2 was measured, and the test method included the following steps: (1) Take 2597 µL of pH 5 0.2 mol / L NaAc-HAc buffer solution, 300 µL of 10 mol / L H2O2 solution, 100 µL of 10 mg / mL TMB solution and 3 μL of 1 mg / mL carbon nitride nanozyme solution and mix them in a centrifuge tube within 30 s.
[0055] (2) The catalytic kinetic curves at 652 nm were detected using the time-driven mode of the UV-visible spectrometer. The enzyme activity determination results are shown in Table 1.
[0056] Table 1 Enzyme activity (U / mg) Example 1 38.45 Example 2 32.48 Example 3 28.21 Example 4 22.46 Example 5 15.89 Example 6 13.67 Example 7 10.29 Example 8 8.09 Example 9 7.88 Example 10 7.43 Comparative Example 1 0.01 Comparative Example 2 0.02 It can be concluded from Table 1 that by comparing Example 1 with Examples 2 and 3, it can be seen that divalent copper salt will affect the activity of the obtained double heteroatom doped carbon nitride nanozyme; by comparing Example 1 with Examples 4 to 7, it can be seen that the ratio of urea and melamine will affect the activity of the obtained double heteroatom doped carbon nitride nanozyme; by comparing Example 1 with Examples 8, 9 and 10, it can be seen that the ratio of carbon nitride and oxalic acid will affect the activity of the obtained double heteroatom doped carbon nitride nanozyme; by comparing Example 1 with Comparative Examples 1 and 2, it can be seen that copper and oxygen have a synergistic effect, and the two synergistically enhance the activity of the double heteroatom doped carbon nitride nanozyme. Test Example 3
[0057] In this test example, the catalytic activity of the double heteroatom-doped carbon nitride nanozymes obtained in Example 1, Example 2 and Example 3 was measured, and the test method included the following steps: (1) Take 2880 µL of pH 5 buffer solution containing 0.2 M sodium hydrogen phosphate and 0.1 M citric acid, 30 µL of 1 mol / L H2O2 solution, 60 µL of 25 mmol / L TMB solution and 30 μL of 10 mg / mL nanozyme solution and mix them in a centrifuge tube. The mixing time is controlled within 30 s. (2) The catalytic kinetic curves at 652 nm were detected using the time-driven mode of the UV-visible spectrometer.
[0058] The results are as follows Fig.10 As shown, the double heteroatom doped carbon nitride nanozyme of Example 1 has the highest catalytic activity, and different copper doping amounts will affect the activity of the prepared carbon nitride nanozyme. Test Example 4
[0059] In this test example, the catalytic activity of the carbon nitride nanozymes obtained in Example 1, Comparative Example 1 and Comparative Example 2 was measured, and the test method included the following steps: (1) Take 2880 µL of pH 5 buffer solution containing 0.2 M sodium hydrogen phosphate and 0.1 M citric acid, 30 µL of 1 mol / L H2O2 solution, 60 µL of 25 mmol / L TMB solution and 30 μL of 10 mg / mL nanozyme solution and mix them in a centrifuge tube. The mixing time is controlled within 30 s. (2) The catalytic kinetic curves at 652 nm were detected using the time-driven mode of the UV-visible spectrometer.
[0060] The results are as follows Fig.11 As shown, the double heteroatom-doped carbon nitride nanozyme of Example 1 has the highest catalytic activity, and different doping of copper and oxygen will affect the activity of the prepared carbon nitride nanozyme. Test Example 5
[0061] In this test example, the double heteroatom-doped carbon nitride nanozyme prepared in Example 1 was subjected to colorimetric detection of glutathione (GSH), and the test method included the following steps: (1) Take 2880 µL of pH 5 buffer solution containing 0.2 M sodium hydrogen phosphate and 0.1 M citric acid, 30 µL of 1 mol / L H2O2 solution, 60 µL of 25 mmol / L TMB solution and 30 μL of 10 mg / mL nanozyme solution and mix them in a centrifuge tube. The mixing time is controlled within 30 s. (2) The absorbance change of the system at 652 nm after 10 min of reaction was detected using the time-driven mode of the UV-visible spectrometer.
[0062] The results are as follows Fig.12 As shown in a, when the double heteroatom-doped carbon nitride nanozyme of Example 1 detects glutathione, as the concentration of glutathione increases, the absorbance of the UV-visible absorption spectrum gradually decreases, and the characteristic absorption peak at 652nm gradually decreases. Fig.12 As shown in b, within the GSH concentration range of 0-75 μM, ∆A 652 There is a good linear relationship between the concentration of GSH and the calculated detection limit LOD is 0.64 μM (3σ). Compared with other GSH colorimetric methods, this method has the advantages of wide linear range and low detection limit (Table 2).
[0063] Table 2 Analytical methods Nanozymes Linear range (μM) Detection limit (μM) References Colorimetry Cu-MOF 0.97-100 0.97 [1] Colorimetry <![CDATA[Mn3O4]]> 5-60 0.889 [2] Colorimetry PCN-224-Mn 0.5-60 0.233 [3] Colorimetry <![CDATA[Ni 4.8 Fe-MOF*-200℃-1h]]> 10-400 1.88 [4] Colorimetry CuOCN 0-75 0.64 The present invention 1.Wang J, Li W, Zheng Y Q. Nitro-functionalized metal–organicframeworks with catalase mimic properties for glutathione detection[J].Analyst, 2019, 144(20): 6041-6047. 2.Xi J, Zhu C, Wang Y, et al. Mn3O4microspheres as an oxidase mimic for rapid detection of glutathione[J]. RSC advances, 2019, 9(29): 16509-16514. 3.Lai 4.Cheng X, Zhou In summary, the present invention successfully prepared a double heteroatom doped carbon nitride nanozyme. Copper and oxygen have the ability to synergistically enhance the enzyme activity. The obtained double heteroatom doped carbon nitride nanozyme can efficiently catalyze the color development reactions of TMB, ABTS and OPD. The preparation method is simple and the raw materials are economical. The enzyme activity of the obtained product has significantly higher peroxidase-like activity than that of the nanozymes reported in most literatures, and the activity is close to that of commercially available natural horseradish peroxidase, and has broad application potential.
[0064] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.
Claims
1. A double heteroatom doped carbon nitride nanozyme, characterized in that: The carbon nitride nanozyme contains copper-oxygen diheteroatoms, in which the mass ratio of copper to oxygen is 1:(20-80). In the carbon nitride nanozyme, the mass ratio of carbon nitride to oxygen is 1:0.
4.
2. A method for preparing the double heteroatom doped carbon nitride nanozyme as claimed in claim 1, characterized in that: The preparation method of the carbon nitride nanozyme comprises mixing and grinding urea, melamine, oxalic acid and a metal salt in a mortar, and then calcining to obtain the carbon nitride nanozyme; the metal salt comprises a divalent copper salt.
3. The method for preparing double heteroatom-doped carbon nitride nanozyme according to claim 2, characterized in that: The divalent copper salt includes any one of copper nitrate, copper chloride, copper sulfate, copper acetate or copper carbonate, or a combination of at least two thereof; and the copper nitrate includes copper nitrate trihydrate.
4. The method for preparing double heteroatom-doped carbon nitride nanozyme according to claim 2, characterized in that: The mass ratio of copper to oxygen in the copper-oxygen diatoms is 1:(20-80).
5. The method for preparing double heteroatom-doped carbon nitride nanozyme according to claim 2, characterized in that: The mass ratio of the urea to melamine is 1:(0-1).
6. The method for preparing double heteroatom-doped carbon nitride nanozyme according to claim 2, characterized in that: The calcination is carried out by uniform heating, the speed of the uniform heating is 2-5°C / min, and the terminal temperature of the uniform heating is 500-600°C; After the uniformly increased temperature reaches the end temperature, the calcination is maintained for 2-5 hours; The protective gas for the calcination includes nitrogen or argon.
7. Application of the double heteroatom doped carbon nitride nanozyme as claimed in claim 1 in analyzing and detecting glutathione.
Citation Information
Patent Citations
Oxygen-doped carbon nitride modified nano calcium peroxide composite photocatalyst as well as preparation method and application thereof
CN115999606A
Preparation method and application of nanoscale oxygen-doped nitrogen-rich carbon nitride
CN118598085A
Graphite-phase carbon nitride quantum dot compound as well as synthesis method and biological application thereof
CN110982521A
Preparation method of potassium-oxygen co-doped graphite phase carbon nitride photocatalyst
CN115007182A
Carbon nitride nano-enzyme as well as preparation method and application thereof
CN118491556A